The Influence of Information Technology and Communication Supply Chain Management Performance for Greater SME Manufacturing in Aguascalientes - Castorena, Octavio Hernández; Enríquez, Luis Aguilera; Adame, Martha González (International Journal of Business, Economics and Management, 2014)
In this research, it aims to show how the information technology and communication (ICT) have influence on the supply chain management in manufacturing SMEs, likewise, analyze how it affects this relationship to operational performance in these organizations, however, for these companies, not all ICT can be adapted to any business, results of the statistical analysis indicate that employers in their interest to adopt ICTs require taking into account the complexity the supply chain to ensure that adoption is not a bad investment and especially the approach to maximize performance in these organizations. The research was conducted with a random sample of 120 SMEs in the manufacturing sector in Aguascalientes during the months of March and April 2012 through a survey designed under the technical fieldwork aimed at managers responsible for coordinating operations Manufacturing of SMEs. The analysis in this study implies that employers establish strategies to enable all workers to improve their skills in the subject of ICT and in this sense, the results are to be useful for decision making and for the better Management of supply chain.